2011
DOI: 10.1002/bip.21581
|View full text |Cite
|
Sign up to set email alerts
|

Conformational preferences and pKa value of selenocysteine residue

Abstract: The conformational preferences of the L-selenocysteine (Sec) dipeptides with selenol and selenolate groups (Ac-Sec-NHMe and Ac-Sec(-) -NHMe, respectively) and the apparent (i.e., macroscopic) pK(a) value of the Sec residue have been studied using the dispersion-corrected density functionals M06-2X and B2PLYP-D with the implicit solvation method in the gas phase and in water. In the gas phase, the backbone-to-backbone and/or side chain-to-backbone hydrogen bonds are found to contribute in stabilizing the most p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 40 publications
1
24
0
2
Order By: Relevance
“…[210] Selenols are much more nucleophilic than thiols mainly because of the greater polarizability of selenium compared to sulfur. [211] Moreover,a lkyl selenols are quite acidic (pK a % 5-7), [211] making the selenolate the dominant form of Sec at physiological pH. Both factors make Sec an appealing bioconjugation handle for site-selective protein modification with electrophiles such as maleimides.…”
Section: Arylation Of Oxidized Selenocysteine Electrophilesmentioning
confidence: 99%
“…[210] Selenols are much more nucleophilic than thiols mainly because of the greater polarizability of selenium compared to sulfur. [211] Moreover,a lkyl selenols are quite acidic (pK a % 5-7), [211] making the selenolate the dominant form of Sec at physiological pH. Both factors make Sec an appealing bioconjugation handle for site-selective protein modification with electrophiles such as maleimides.…”
Section: Arylation Of Oxidized Selenocysteine Electrophilesmentioning
confidence: 99%
“…23, 24 Compared to its cysteine counterpart (pKa = ~ 8), Sec has a lower pKa (~ 5) and enhanced nucleophilicity, which permits selective Sec conjugation in the presence of cysteines and other natural amino acids. 25 Based on this property, we have introduced a unique class of selenocysteine (Sec)-modified antibodies (SELENOMABS) that allow site-specific antibody modification leading to homogeneous ADCs. 26, 27 Furthermore, we demonstrated that SELENOMAB-oxadiazole conjugates had enhanced stability relative to maleimide counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…[210] Selenole sind wesentlich nukleophiler als Thiole,w as auf die ausgeprägtere Polarisierbarkeit von Selen zurückgeht. [211] Außerdem sind Alkylselenole recht acide (pK a % 5-7), [211] weswegen Selenocystein bei physiologischem pH-Wert hauptsächlich in der Selenolatform vorliegt. Ausd iesen Gründen stellt Selenocystein einen vielversprechenden Ankerpunkt fürd ie regioselektive Proteinmodifikation mit Elektrophilen wie Maleimid dar.…”
Section: Arylierung Oxidierter Selenocystein-elektrophileunclassified